Valuing Children’s Expression: A first attempt at displaying preschool art in an early childhood centre - Itzkowitz, Selina (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
A local childcare centre embarks on a first-time project to exhibit preschool children’s artworks, acknowledging the importance of art-based activities in the development of young children. In the planning and implementation of a successful afternoon event, the centre’s children, along with parents, other family members, friends, and educators, were able to appreciate the variety of techniques and materials used to create the skillfully-planned exhibit. The author provides insights into the challenges of undertaking such an endeavor and makes recommendations to promote its success.